Isolation of legionella from cooling towers and potable water systems in Hospital and non-medical buildings in a University campus - Ching, K.S.; Rosli, A.A.; Wee, C.S.L.; Ngeow, Y.F. (Faculty of Medicine, University of Malaya, 2005)
Six cooling towers and eleven sources of potable water in a university campus in Kuala Lumpur were surveyed for the presence of legionellae. One non-medical building cooling tower and three hot water systems from one ward of the hospital tested positive for Legionella, two of which contained Legionella pneumophila serogroup 1. The identification of Legionella was based on isolation, immunofluorescence and polymerase chain reaction (PCR).